Pancasila as a Philosophical System - Marzuki, Marzuki; Ansor Hasibuan; Zaskia Nur Sakina; Muhammad Fahmi Arifin (Sean Institute, 2025)
Pancasila is the ideological framework of the Indonesian state. It consists of the basic principles that have helped the country develop since gaining its independence in 1945. Pancasila is not only a political system, but also a philosophical structure that combines five main principles: Almighty God, Just and Civilized Humanity, Unity of Indonesia, Democracy guided by wisdom in deliberation and representation, and Social Justice for All Indonesian People. This article will look at how Pancasila emerged, developed, and influenced Indonesian society, government, and culture. In addition, we will look at how Pancasila as a philosophical system has shaped state policy, defined national identity, and contributed to the development of morality and ethics in everyday life.